Development of jacket substructure systems supporting 3MW offshore wind turbine for deep water sites in South Korea - Thanh-Tuan Tran (International Journal of Naval Architecture and Ocean Engineering, 2022)
This study aims to develop jacket substructures supporting a 3MW Offshore Wind Turbine (OWT) in water depth ranges of 25–40 m. A simplified structural design process is introduced and influences of jacket topological forms and brace systems on their dynamic performances are assessed. The results conclude that the topological configuration of the jacket substructure has a significant influence on the dynamic characteristics of the whole system, indicating a high priority when designing a jacket substructure for OWTs. Furthermore, two jacket substructures having the lowest material costs and the best performances under the Korean ocean environmental conditions are suggested. Additionally investigated in this study is a sensitivity of environmental loading directions on the structural performances of the jacket substructures. All the findings in this study might be very useful to assist the structural engineers when they design the support structures for large-scaled OWTs in the near future in South Korea.